Anisotropic conductive film and preparation method thereof

By setting a groove structure on the surface of the transfer roller and filling conductive particles, combined with the use of a modified silane coupling agent, the problem of insufficient resistance of the existing conductive film is solved, and a bonding packaging effect with high precision and narrow spacing is achieved.

CN119673562APending Publication Date: 2025-03-21CHINA EUROPE ELECTRONIC MATERIALS INT INNOVATION CENT (HEFEI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411841331.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing anisotropic conductive films have shortcomings in resistance reliability and cannot meet the requirements of high-precision, narrow-pitch bonded packaging.

Method used

By providing an array groove structure on the surface of the transfer roller and filling the groove with conductive particles, combined with the use of a modified silane coupling agent, an anisotropic conductive film with excellent particle dispersion and resistance reliability was prepared.

Benefits of technology

It improves the self-repair performance and resistance reliability of the conductive film, and meets the requirements of high-precision, narrow-pitch bonded packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673562A_ABST
    Figure CN119673562A_ABST
Patent Text Reader

Abstract

The invention discloses an anisotropic conductive film and a preparation method thereof, and belongs to the technical field of conductive films. A transfer printing roller serves as a carrier, an array type groove structure is arranged on the surface of the transfer printing roller, meanwhile, the transfer printing roller is of a hollow cylinder structure, and multiple scrapers are fixed to the surface of the transfer printing roller; conducting particles are sprayed to the surface of the transfer printing roller in a spraying mode, the grooves are filled with the conducting particles through the multiple scrapers along with rotation of the transfer printing roller, and each groove is filled with two conducting particles; placing an insulating resin adhesive film and a PET (Polyethylene Terephthalate) base film below the transfer printing roller; a roller shaft of a double roller rotating synchronously with the transfer printing roller is placed below the PET base film; and when the transfer printing roller and the roller shaft of the pair roller rotate synchronously, the winding and unwinding device of the insulating resin adhesive film winds and unwinds the adhesive film synchronously, so that the conductive particles are arranged on the insulating resin adhesive film in an array manner, and the anisotropic conductive film is obtained. The anisotropic conductive film prepared by the invention has excellent resistance reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive films, and in particular relates to an anisotropic conductive film and a preparation method thereof. Background Art

[0002] At present, with the rapid development of microelectronics technology, electronic parts are gradually miniaturized and micro-miniaturized, so some electronic parts and substrates need a narrower spacing connection technology. Compared with the previous solder bonding process, anisotropic (ACF) conductive film has significant advantages in preparation process, bonding temperature, bonding strength, bonding spacing, environmental protection, price cost, application range, etc. It is more suitable for high-density, narrow-pitch bonding packaging of devices such as LCD screens and MicroLEDs, and will have broad application prospects in various circuit packaging and electronic device fields in the future.

[0003] The basic feature of ACF conductive film is to use adhesive film to connect electronic parts and substrates. After pressurization, the conductive particles in it connect the electronic parts and substrates in the vertical circuit and insulate in the horizontal direction. ACF conductive film is mainly divided into two types, one is a conductive film with irregular particle arrangement, and the other is a conductive film with particle array arrangement. The method of making randomly arranged conductive film is very simple. The conductive particles are mixed with glue by mechanical stirring, ultrasound or adding dispersant, and then the ACF conductive film can be obtained by coating. However, the conductive film has the disadvantages of particle aggregation and poor uniformity. During use, it is easy to have the risk of lateral short circuit between electrodes, which reduces the yield rate of the product, and therefore cannot meet the requirements of high-precision, narrow-pitch bonding packaging. In the array-arranged conductive film, each conductive particle is completely independent in the form of an array, which can effectively solve the problems of particle aggregation and poor uniformity of the conductive film. Therefore, the array-arranged conductive film is currently widely used in the packaging of various micro devices.

[0004] There are many methods for making conductive films with particle arrays, including nanoimprinting, microcavity loading, photolithography, electrostatic adsorption, etc. However, these methods require extremely high process routes and equipment technology, which will lead to the disadvantages of high production costs and low production efficiency, and there are also problems such as missing filling particles and damage to conductive particles during the production and preparation process. Therefore, further reducing the production cost of conductive films and improving the product quality of conductive films are important research directions in the field of microelectronics packaging, and are also of great significance for the future product development and production of industries such as screen displays. Therefore, it is urgent to develop a new method for making anisotropic conductive films.

[0005] Patent CN118098705A discloses a method for preparing an anisotropic conductive film with an array arrangement of conductive particles. The patent directly processes an arrayed open cavity on the surface of a roller to achieve a uniform arrangement of conductive particles. The conductive particles filled into the open cavity are easily transferred out, reducing the formation of transfer defects and improving the transfer rate of conductive particles. At the same time, the array arrangement method can be designed according to actual needs, with high flexibility, and precise control of the filling of conductive particles can be achieved. However, the anisotropic conductive film prepared by this patent and the prior art still has the disadvantage of poor resistance reliability. Summary of the invention

[0006] The object of the present invention is to provide an anisotropic conductive film and a preparation method thereof, so as to solve the disadvantage that the anisotropic conductive film prepared by the prior art still has poor resistance reliability.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing an anisotropic conductive film, comprising the following steps:

[0009] S1: Using a transfer roller as a carrier, an array groove structure is arranged on the surface of the transfer roller. At the same time, the transfer roller is a hollow cylindrical structure, a cylindrical magnet is arranged in the hollow part inside, and multiple scrapers are fixed on the surface;

[0010] S2: Spray the conductive particles onto the surface of the transfer roller. As the transfer roller rotates, multiple scrapers fill the conductive particles into the grooves, with two conductive particles in each groove;

[0011] S3: placing an insulating resin film and a PET base film under the transfer roller;

[0012] S4: placing a pair of rollers rotating synchronously with the transfer roller under the PET base film, and embedding a rubber layer on the surface of the pair of rollers;

[0013] S5: While the transfer roller and the counter roller shaft rotate synchronously, the winding and unwinding device of the insulating resin film simultaneously winds and unwinds the film, thereby arranging the conductive particles in an array on the insulating resin film to obtain anisotropic conductive films.

[0014] Furthermore, the groove shape is designed to be a trapezoidal cavity structure, with one side wall perpendicular to the opening surface and a corresponding side wall inclined, the ratio of the width at the opening to the deepest width is 4:3, the groove array is arranged as a square lattice arrangement, the spacing between the center points of each groove is 3-4 times the diameter of the conductive particle, and the ratio of the groove depth to the diameter of the conductive particle is 0.8-1.2; the groove length is 2.2-2.5 times the diameter of the conductive particle; the width of the groove opening is 1.5-1.8 times that of the conductive particle.

[0015] In this case, the conductive particles are easily filled into the grooves under the action of the scraper, and the conductive particles are also easily transferred out during the roller printing process, which is beneficial to improving the filling rate and transfer rate of the conductive particles.

[0016] Furthermore, the transfer roller is made of any one of metal, ceramic or plastic materials; the roller shaft is made of any one of metal, ceramic or plastic materials; the rubber layer embedded on the surface of the roller shaft is any one of nitrile rubber, polyurethane rubber and acrylic rubber.

[0017] Furthermore, the conductive particles are spherical with a diameter of 2-5 μm, the core is a polystyrene ball, the surface is electroplated to cover a metal coating such as nickel or silver, and a polystyrene organic insulating layer is formed outside the metal coating. The organic insulating layer formed outside the metal coating can prevent short circuits from occurring during circuit connection.

[0018] Furthermore, the multiple scrapers are two or three polyurethane scrapers, and the scrapers and the cross-sections in the rotation direction of the roller form an angle of 45° to 135°.

[0019] Furthermore, the process of filling the groove with conductive particles is as follows: the conductive particles are pre-configured with a low boiling point solvent to form a mixed solution at a mass ratio of 1:4, and the low boiling point solvent is any one of ethanol, ethyl acetate, butanone, and toluene.

[0020] Furthermore, the thickness of the insulating resin film is 3-10 um.

[0021] Furthermore, the preparation method of the insulating resin film is:

[0022] A1: In parts by weight, weigh 30-50 parts of a film-forming resin, 10-15 parts of a toughening resin, 5-10 parts of a reactive resin, 5-20 parts of polyvinyl butyral, 5-10 parts of a curing agent, 0.2 parts of a chain transfer agent, 0.1 parts of a stabilizer, 0.2-0.6 parts of a modified silane coupling agent, and 15-40 parts of a thixotropic agent to obtain a mixture;

[0023] A2: The mixture is mixed with toluene solvent and stirred to obtain a glue with a solid content of 50%;

[0024] A3: After degassing the glue, apply it on the PET base film and dry it to obtain an insulating resin film.

[0025] Furthermore, the weight average molecular weight of the film-forming resin is 10,000-150,000, and the film-forming resin includes at least one of phenoxy resin, epoxy resin, and polyurethane resin.

[0026] Furthermore, the toughening resin has a weight average molecular weight of 300-10000 and includes at least one of alicyclic epoxy resin, polyether-modified epoxy resin, silicone-modified epoxy resin, and polyurethane-modified epoxy resin.

[0027] Furthermore, the reactive resin has a weight average molecular weight of 200-10000 and a viscosity of 200-50000 cps, and includes at least one of alicyclic epoxy resin, phenolic epoxy resin, naphthalene epoxy resin, phenol biphenyl epoxy resin, and hydrogenated bisphenol epoxy resin.

[0028] Furthermore, the curing agent is CXC-1612, the chain transfer agent is ethylene glycol, the stabilizer is propylene carbonate, and the thixotropic agent is gas-phase SiO2.

[0029] Furthermore, the preparation method of the modified silane coupling agent is:

[0030] 3-aminopropyltrimethoxysilane and 1H,1H,2H-perfluorooctanal were dissolved in anhydrous DMF, stirred for 30 minutes, cooled to 2°C, added with sodium borohydride, reacted at room temperature for 90 minutes, extracted with anhydrous ether, filtered, and dried to obtain a modified silane coupling agent;

[0031] Among them, the usage ratio of 3-aminopropyltrimethoxysilane, 1H,1H,2H-perfluorooctanal, anhydrous DMF and sodium borohydride is 0.59g:1.19g:20mL:0.07g.

[0032] In the above reaction, the amino group of 3-aminopropyltrimethoxysilane and the aldehyde group of 1H,1H,2H-perfluorooctanal react with Schiff base to form an imine bond, thereby obtaining a modified silane coupling agent. The imine bond is a dynamic covalent carbon-nitrogen double bond that is reversible at room temperature. The self-repair process of the imine bond is a dynamic equilibrium process. Inside the material, the imine bond breaks and reorganizes continuously, allowing the material to self-repair to a certain extent and maintain its integrity and performance. 1H,1H,2H-perfluorooctanal is a perfluorinated aldehyde compound, which contains a large number of fluorine atoms in its molecular structure. Fluorine atoms have extremely high electronegativity and can form stable covalent bonds, thereby enhancing the chemical stability and thermal stability of the compound. Perfluorinated compounds usually have low surface energy, which makes them less likely to absorb water or hydrolyze in high humidity environments. When applied to anisotropic conductive films, they can improve their resistance reliability in high temperature and high humidity environments.

[0033] In a second aspect, the present invention provides an anisotropic conductive film prepared by the above-mentioned method for preparing the anisotropic conductive film.

[0034] Beneficial effects of the present invention:

[0035] The present invention can improve the self-healing performance and resistance reliability of the anisotropic conductive film by adding a modified silane coupling agent during the preparation of the anisotropic conductive film, and the present invention can make the anisotropic conductive film have an excellent particle dispersion rate by controlling the groove shape and the number of conductive particles filled in each groove. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The present invention will be further described below in conjunction with the accompanying drawings.

[0037] Figure 1 is a schematic diagram of a groove array on a transfer roller of the present invention;

[0038] Figure 2 Schematic diagram of the cross section and array of the groove of the transfer roller filled with conductive particles of the present invention;

[0039] Figure 3 It is a schematic diagram of the arrangement of conductive particle arrays on the surface of the anisotropic conductive film of the present invention;

[0040] Figure 4 1. It is a three-dimensional view and a cross-sectional view of the transfer roller of the present invention;

[0041] Figure 5 It is a schematic diagram of the conductive particle transfer process of the present invention;

[0042] Figure 6 It is a schematic diagram of the anisotropic conductive film bonding multi-terminal FPC and ITO glass of the present invention.

[0043] In the attached figure: 1. transfer roller surface; 2. grooves; 3. conductive particles; 4. insulating resin film; 5. transfer roller; 6. cylindrical magnet; 7. counter roller; 8. PET base film; 9. multiple scrapers; 10. anisotropic conductive film; 11. multi-terminal FPC; 12. I TO glass. DETAILED DESCRIPTION

[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] This embodiment provides a method for preparing an anisotropic conductive film, comprising the following steps:

[0047] S1: Using a transfer roller 5 as a carrier, an array groove 2 structure is arranged on the surface 1 of the transfer roller. Meanwhile, the transfer roller 5 is a hollow cylindrical structure, a cylindrical magnet 6 is arranged in the hollow part thereof, and multiple scrapers 9 are fixed on the surface;

[0048] S2: The conductive particles 3 are sprayed onto the surface 1 of the transfer roller. As the transfer roller 5 rotates, the multiple scrapers 9 fill the conductive particles into the grooves 2, with two conductive particles in each groove 2;

[0049] S3: placing an insulating resin film 4 and a PET base film 8 under the transfer roller 5;

[0050] S4: placing a counter-roller shaft 7 that rotates synchronously with the transfer roller 5 under the PET base film 8, and a rubber layer is embedded on the surface of the counter-roller shaft 7;

[0051] S5: While the transfer roller 5 and the counter roller shaft 7 rotate synchronously, the unwinding and rewinding device of the insulating resin film 4 simultaneously rewinds and unwinds the film, thereby arranging the conductive particles 3 in an array on the insulating resin film 4 to obtain anisotropic conductive films.

[0052] The shape of the groove 2 is designed to be a trapezoidal cavity structure, with one side wall perpendicular to the opening surface and a corresponding side wall inclined. The ratio of the width at the opening to the width at the deepest point is 4:3. The groove 2 array is arranged in a square lattice arrangement. The spacing between the center points of each groove 2 is 3.5 times the diameter of the conductive particle 3. The groove 2 is 2.5μm deep and 7μm long. The width of the groove 2 at the opening is 4.5μm.

[0053] The transfer roller 5 is made of metal nickel, the counter roller shaft 7 is made of metal nickel, and the rubber layer embedded on the surface of the counter roller shaft 7 is nitrile rubber.

[0054] The conductive particles 3 are spherical with a diameter of 3 μm. The inner core is a polystyrene sphere. The surface is covered with a metal coating such as nickel or silver by electroplating, and a polystyrene organic insulating layer is formed outside the metal coating.

[0055] The multiple scrapers 9 are three polyurethane scrapers, and the scrapers and the tangent planes in the direction of rotation of the roller form 90 degrees.

[0056] The process of filling the groove 2 with the conductive particles 3 is as follows: the conductive particles 3 are preliminarily prepared with a low boiling point solvent into a mixed solution at a mass ratio of 1:4, and the low boiling point solvent is ethyl acetate.

[0057] The thickness of the insulating resin film 4 is 5 μm.

[0058] The preparation method of the insulating resin film 4 is as follows:

[0059] A1: In parts by weight, 40 parts of phenoxy resin PKHH, 10 parts of alicyclic epoxy resin CELLOXIDE8010, 5 parts of alicyclic epoxy resin CELLOXIDE 2021P, 5 parts of polyvinyl butyral, 5 parts of curing agent CXC-1612, 0.2 parts of ethylene glycol, 0.1 parts of propylene carbonate, 0.6 parts of modified silane coupling agent, and 30 parts of gas-phase SiO2 were weighed to obtain a mixture;

[0060] A2: The mixture is mixed with toluene solvent and stirred to obtain a glue with a solid content of 50%;

[0061] A3: After degassing the glue, apply it on the PET base film and dry it to obtain an insulating resin film.

[0062] The preparation method of the modified silane coupling agent is:

[0063] 3-aminopropyltrimethoxysilane and 1H,1H,2H-perfluorooctanal were dissolved in anhydrous DMF, stirred for 30 minutes, cooled to 2°C, added with sodium borohydride, reacted at room temperature for 90 minutes, extracted with anhydrous ether, filtered, and dried to obtain a modified silane coupling agent;

[0064] Among them, the usage ratio of 3-aminopropyltrimethoxysilane, 1H,1H,2H-perfluorooctanal, anhydrous DMF and sodium borohydride is 0.59g:1.19g:20mL:0.07g.

[0065] Example 2

[0066] The difference between this embodiment and Embodiment 1 is that the "groove depth 2.5 μm, length 7 μm, groove opening width 4.5 μm" in Embodiment 1 is replaced by "groove depth 3.5 μm, length 7.5 μm, groove opening width 5 μm", and the remaining raw materials and steps are the same as Embodiment 1.

[0067] Example 3

[0068] The difference between this embodiment and Embodiment 1 is that the "groove depth 2.5 μm, length 7 μm, groove opening width 4.5 μm" in Embodiment 1 is replaced by "groove depth 3 μm, length 7 μm, groove opening width 5 μm", and the remaining raw materials and steps are the same as Embodiment 1.

[0069] Example 4

[0070] The difference between this embodiment and embodiment 1 is that the "the section of the scraper and the roller in the rotation direction is 90°" in embodiment 1 is replaced by "the section of the scraper and the roller in the rotation direction is 135°", and the remaining materials and steps are the same as embodiment 1.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that the "the scraper and the cross-section in the direction of rotation of the roller are 90 degrees" in embodiment 1 is replaced by "the scraper and the cross-section in the direction of rotation of the roller are 45 degrees", and the remaining materials and steps are the same as in embodiment 1.

[0073] Example 6

[0074] The difference between this embodiment and embodiment 1 is that "0.6 parts of modified silane coupling agent, 30 parts of gas-phase SiO2" in embodiment 1 is replaced by "0.4 parts of modified silane coupling agent, 20 parts of gas-phase SiO2", and the remaining raw materials and steps are the same as embodiment 1.

[0075] Example 7

[0076] The difference between this embodiment and embodiment 1 is that "0.6 parts of modified silane coupling agent, 30 parts of gas-phase SiO2" in embodiment 1 is replaced by "0.2 parts of modified silane coupling agent, 20 parts of gas-phase SiO2", and the remaining raw materials and steps are the same as in embodiment 1.

[0077] Comparative Example 1

[0078] Compared with Example 1, the difference between this comparative example and Example 1 is that "two conductive particles are filled in each groove 2" and "the groove depth is 2.5 μm, the length is 7 μm, and the width at the groove opening is 4.5 μm" in Example 1 are replaced by "one conductive particle is filled in each groove 2" and "the groove depth is 2.5 μm, the length is 7 μm, and the width at the groove opening is 4.5 μm", and the remaining raw materials and steps are the same as Example 1.

[0079] Comparative Example 2

[0080] Compared with Example 1, the difference between this comparative example and Example 1 is that the "groove (2) shape is designed to be a trapezoidal cavity structure" and "groove depth 2.5μm, length 7μm, groove opening width 4.5μm" in Example 1 are replaced by "groove (2) shape is designed to be a rectangular cavity structure" and "groove depth 2.5μm, length 7μm, groove opening width 4μm", and the remaining raw materials and steps are the same as Example 1.

[0081] Comparative Example 3

[0082] Compared with Example 1, this comparative example is different in that no fumed silica is added, and the other raw materials and steps are the same as Example 1.

[0083] Comparative Example 4

[0084] Compared with Example 1, this comparative example is different in that the modified silane coupling agent is replaced by 3-aminopropyltrimethoxysilane, and the other raw materials and steps are the same as Example 1.

[0085] The anisotropic conductive films obtained in Examples 1 to 8 and Comparative Examples 1 to 4 were tested for performance, and the results are shown in Table 1:

[0086] 1. Particle dispersion rate and on-resistance test: The anisotropic conductive films obtained in Examples 1 to 8 and Comparative Examples 1 to 2 were attached to the surface of ITO glass, and an FPC bonding machine was used to bond the FPC substrate and the ITO glass through the anisotropic conductive film. The bonding temperature was 150°C, the bonding time was 90 seconds, and the bonding pressure was 50 MPa. The on-resistance of the bonded substrate was tested with a multimeter, and then the bonded substrate was placed in an environment with a temperature of 85 degrees and a humidity of 85 degrees for 500 hours using an optical microscope and Image-Pro P l us processing software, and the on-resistance of the substrate was tested again.

[0087] 2. Self-repairing performance test: scratches with a length of 200nm, a width of 20μm, and a depth of 30μm were made on the surface of the sample. The sample was placed under 80% humidity and 25°C for 24 hours for self-repair. The on-resistance before and after the scratch test was measured. The ratio represents the self-repairing property and is recorded as the self-repair rate.

[0088] Table 1

[0089]

[0090]

[0091] As can be seen from Table 1, the anisotropic conductive films prepared in Examples 1 to 8 have excellent resistance reliability and self-healing properties. In Comparative Example 1, the groove of the transfer roller can only accommodate one conductive particle, and the particle dispersion is poor, indicating that the use of groove holes that accommodate two particles for particle transfer can improve the particle dispersion on the surface of the film. In Comparative Example 2, the groove structure is a rectangular cavity structure, and the particle dispersion is poor, indicating that the use of groove holes with a trapezoidal structure for particle transfer can improve the particle dispersion on the surface of the film. In Comparative Example 3, no gas-phase silica is added, and its resistance reliability and self-healing performance are reduced, indicating that gas-phase silica can improve resistance reliability and self-healing performance. In Comparative Example 4, the modified silane coupling agent is replaced with 3-aminopropyltrimethoxysilane, and its resistance reliability and self-healing performance are reduced, indicating that the modified silane coupling agent improves resistance reliability and self-healing performance.

[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing anisotropic conductive films, characterized in that: The steps include: S1: Using a transfer roller (5) as a carrier, an array groove (2) structure is arranged on the surface (1) of the transfer roller, and the transfer roller (5) is a hollow cylindrical structure, a cylindrical magnet (6) is arranged in the hollow part thereof, and multiple scrapers (9) are fixed on the surface; S2: The conductive particles (3) are sprayed onto the surface of the transfer roller (1), and as the transfer roller (5) rotates, the multiple scrapers (9) fill the conductive particles into the grooves (2), with two conductive particles being filled into each groove (2); S3: placing an insulating resin film (4) and a PET base film (8) under the transfer roller (5); S4: placing a counter-roller shaft (7) that rotates synchronously with the transfer roller (5) under the PET base film (8), and a rubber layer is embedded on the surface of the counter-roller shaft (7); S5: While the transfer roller (5) and the counter roller shaft (7) rotate synchronously, the winding and unwinding device of the insulating resin film (4) simultaneously winds and unwinds the film, thereby arranging the conductive particles (3) in an array on the insulating resin film (4) to obtain anisotropic conductive films.

2. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The shape of the groove (2) is designed to be a trapezoidal cavity structure, one side wall is perpendicular to the opening surface, and the corresponding side wall is inclined, the ratio of the width at the opening to the width at the deepest point is 4:3, the groove (2) array is arranged in a square lattice arrangement, the spacing between the center points of each groove (2) is 3-4 times the diameter of the conductive particle (3), the ratio of the depth of the groove (2) to the diameter of the conductive particle (3) is 0.8-1.2; the length of the groove (2) is 2.2-2.5 times the diameter of the conductive particle (3); the width of the groove (2) at the opening is 1.5-1.8 times that of the conductive particle.

3. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The transfer roller (5) is made of any one of metal, ceramic or plastic materials; the counter-roller shaft (7) is made of any one of metal, ceramic or plastic materials; the rubber layer embedded on the surface of the counter-roller shaft (7) is made of any one of nitrile rubber, polyurethane rubber and acrylic rubber.

4. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The conductive particles (3) are spherical with a diameter of 2-5 μm. The inner core is a polystyrene sphere. The surface is covered with a metal coating such as nickel or silver by electroplating, and a polystyrene organic insulating layer is formed outside the metal coating.

5. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The multiple scrapers (9) are two or three polyurethane scrapers, and the angle between the scrapers and the cross section of the roller in the rotation direction is 45° to 135°.

6. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The process of filling the groove (2) with the conductive particles (3) is as follows: the conductive particles (3) are preliminarily configured with a low boiling point solvent in a mass ratio of 1:4 to form a mixed liquid, wherein the low boiling point solvent is any one of ethanol, ethyl acetate, butanone and toluene.

7. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The thickness of the insulating resin film (4) is 3-10 um.

8. The method for preparing anisotropic conductive film according to claim 1, characterized in that: The preparation method of the insulating resin film (4) is as follows: A1: In parts by weight, weigh 30-50 parts of a film-forming resin, 10-15 parts of a toughening resin, 5-10 parts of a reactive resin, 5-20 parts of polyvinyl butyral, 5-10 parts of a curing agent, 0.2 parts of a chain transfer agent, 0.1 parts of a stabilizer, 0.2-0.6 parts of a modified silane coupling agent, and 15-40 parts of a thixotropic agent to obtain a mixture; A2: The mixture is mixed with toluene solvent and stirred to obtain a glue with a solid content of 50%; A3: After degassing the glue, apply it on the PET base film and dry it to obtain an insulating resin film; The weight average molecular weight of the film-forming resin is 10,000-150,000, including at least one of phenoxy resin, epoxy resin, and polyurethane resin; the weight average molecular weight of the toughening resin is 300-10,000, including at least one of alicyclic epoxy resin, polyether modified epoxy resin, silicone modified epoxy resin, and polyurethane modified epoxy resin; the weight average molecular weight of the reactive resin is 200-10,000, and the viscosity is 200-50,000 cps, including at least one of alicyclic epoxy resin, phenolic epoxy resin, naphthalene type epoxy resin, phenol biphenyl epoxy resin, and hydrogenated bisphenol epoxy resin; the curing agent is CXC-1612, the chain transfer agent is ethylene glycol, the stabilizer is propylene carbonate, and the thixotropic agent is gas phase SiO2.

9. The method for preparing anisotropic conductive film according to claim 8, characterized in that: The preparation method of the modified silane coupling agent is: 3-Aminopropyltrimethoxysilane and 1H,1H,2H-perfluorooctanal were dissolved in anhydrous DMF, stirred for 30 min, cooled to 2°C, added with sodium borohydride, reacted at room temperature for 90 min, extracted with anhydrous ether, filtered, and dried to obtain a modified silane coupling agent; the dosage ratio of 3-aminopropyltrimethoxysilane, 1H,1H,2H-perfluorooctanal, anhydrous DMF, and sodium borohydride was 0.59 g:1.19 g:20 mL:0.07 g.

10. An anisotropic conductive film, characterized in that: The anisotropic conductive film is prepared by the method for preparing the anisotropic conductive film according to any one of claims 1 to 9.